Systematic Literature Review: Resiliensi matematis dalam pembelajaran matematika - Meilani, Ajeng; Meiliasari, Meiliasari (Universitas PGRI Semarang, 2024)
Students need internal or external support in learning mathematics; the main focus of this study discusses internal factors regarding students' mathematical resilience. This study aims to examine the definition, indicators, and role of mathematical resilience in mathematics learning. Systematic Literature Review (SLR) is a research method used in this study. Before being adjusted to the criteria, there were 38 articles, but only 14 articles in the last 5 years met the criteria as material for reviewing the discussion related to mathematical resilience. The results of the study show that (1) mathematical resilience can be determined to be a non-intellectual capacity of students in mathematics learning, especially the capacity to survive and form a positive mindset in facing all challenges at a difficult level when learning mathematics in class; (2) indicators of mathematical resilience that are often used come from Sumarmo, Johnston-Wilder et al., and Hutauruk; (3) the role of mathematical resilience in learning is to help students control affective abilities in training the abilities needed when learning mathematics. In further research, it is hoped that we will be able to link students' mathematical resilience with appropriate learning models.